(untitled) (Canadian Medical Education Journal, 2020)
Background: Although transition from residency to practice represents a critical learning stage, there is a paucity of literature to inform local curriculum development and implementation. Objectives: To describe local curriculum development for Transition to Practice (TTP) for use within a competency-based medical education model, including important content and suitable teaching and assessment strategies. Design: We reviewed the literature to construct a definition and develop initial curriculum content for TTP. We then gathered local residency program directors’ views on TTP content, teaching, and assessment via online survey and an international educational conference workshop. Results: We identified 21 important TTP content areas in the literature and analyzed 35 survey responses, representing 33 residency programs. Survey participants viewed Further sophistication of clinical skills, How to set up a practice, and Time management skills as the three most important content areas. Views on content importance varied by program. For learning and teaching strategies, most respondents preferred: assessing what residents could do, providing real-life practice opportunities, and offering workplace-based assessments. Conclusions: TTP curricula implementation should reflect nationally set, specialty-specific curriculum elements; locally developed priority content; and learning and teaching strategies. Individual learner needs and imminent practice context should guide faculty approaches to curriculum delivery.